COVID-19 handbook for primary school children (Fun-Facts for Kids). - Yusof, Nurul Asyiqin; Mustapa, Marami; Aung, Sanda (Penerbit UPNM, 2021)
This eBook is designed to educate the primary school children on COVID-19 disease. The little readers will have an overview on the causative agent, symptoms of COVID-19 and how to prevent from being infected by the virus. The authors used simple language to enhance children's understanding on this matter, in a fun way. The illustrations were made in a bright, colorful images to enhance comprehension.